Rola mediów społecznościowych w komunikacji partii politycznych i podejmowaniu decyzji wyborczych przez ich wyborców. - Bodys, Marta (Political Preferences, 2016)
The role of social media in the communication of political parties and the impact of them on voters’ decisions The role of using of social media by the Polish political parties to communicate with internet users is still growing. Aricticle shows how voters are assessing credibility of political parties’ communication in social media and how they evaluate the impact of this communication on their decisions on election day. Article is based on polle results which was conducted after the parliamentary elections in 2015. The voter assessed communiation of political parties such as: Civic Platform, Law and Justice, Kukiz’15, Polisch People’s Party, United Left, .Modern, Together. Key words: social media, election campaign, parliamentary elections, website